2022
DOI: 10.1007/s00167-022-06963-y
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety are associated with worse baseline function in hip arthroscopy patients

Abstract: Purpose The purpose of this study was to analyze the correlation between baseline depression and anxiety and preoperative functional status in hip arthroscopy patients. Methods A prospective, institutional review board-approved orthopaedic registry was used to retrospectively study 104 patients undergoing hip arthroscopy. Enrolled patients were administered baseline questionnaires for Patient-Reported Outcomes Measurement Information System (PROMIS) domains, Musculoskeletal Outcomes Data Evaluation and Managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…In this study, we also demonstrated an association between postoperative complications, including postoperative ipsilateral hip injection, any reoperation and revision hip arthroscopy, and a diagnosis of depression, anxiety, or both, which is consistent with previously published results [8,12]. Unlike other published studies, we did not find significant differences in PROMs between patients with a diagnosis of depression and/or anxiety, and those without these diagnoses, although only a very small subset of patients in this study had PROMs on record [15,32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we also demonstrated an association between postoperative complications, including postoperative ipsilateral hip injection, any reoperation and revision hip arthroscopy, and a diagnosis of depression, anxiety, or both, which is consistent with previously published results [8,12]. Unlike other published studies, we did not find significant differences in PROMs between patients with a diagnosis of depression and/or anxiety, and those without these diagnoses, although only a very small subset of patients in this study had PROMs on record [15,32].…”
Section: Discussionsupporting
confidence: 92%
“…However, given the significant variability in depression and anxiety symptoms and presentation, which vary by sex and age, recognition of previously undiagnosed but clinically relevant pathology can be extremely challenging for orthopedic surgeons [6,13,29]. We therefore advocate for the integration of validated instruments such as PROMIS Anxiety and Depression scales to screen for depression and anxiety in the orthopedic practice setting [15]. This will allow for the identification of patients who may benefit from referral to additional resources.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial factors such as depression and anxiety have shown associations with worse baseline function and poorer outcomes post-surgery [ 25 ]. Patients with symptoms of depression have consistently reported lower initial functional scores, higher pain levels, and reduced satisfaction following HA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%